Geographic Information System for Mapping Agricultural Land in North Samarinda District - Dian Pratiwi Nurdin; Syafei Karim; Nia Kurniadin (Politeknik Pertanian Negeri Samarinda, 2022)
This research is motivated by the unavailability of an information system that facilitates data processing of agricultural land for rice commodities at the Agricultural Extension Center of Suluh Manuntung Lempake and the delivery of information that is easily accessible in the form of a web regarding the mapping of agricultural land and land data for rice commodities. North Samarinda sub-district is the center of food crop agriculture and the most cultivated by the community is rice, which has the largest rice harvest area compared to other sub-districts. Ease of access to that information can be presented in the form of a Geographic Information System or GIS (Geographic Information System). GIS is a system designed to capture, store, manipulate, analyze, organize and display all types of geographic data. The results of this study are to build an information system application to facilitate data processing and delivery of information regarding agricultural land mapping as well as farmer data information and farmer group harvest data in North Samarinda District, which is presented in the form of WebGIS mapping of agricultural land for rice commodities, for public knowledge. That the District of North Samarinda has the potential to produce plants that are beneficial to the community.